The quality of life after Anterior Cervical Discectomy and Fusion - Gabriela Zapolska; Małgorzata Kowalska; Zenon Mariak; Ewa Matuszczak; Robert Milewski; Łukasz Matus; Adam Hermanowicz (Kazimierz Wielki University, 2024)
Cervical discopathy is commonly associated with pain in the cervical spine which may affect patients' quality of life. If conservative treatment fails to relieve the pain for at least 6 months and/or if neurological deficit progresses, the surgical treatment is taken under consideration. The aim of this study was to evaluate health-related quality of life (HRQOL) and disability of patients after single- and multi-level anterior cervical discectomy and fusion (ACDF) with standalone polyetheretherketone (PEEK) cages. The study evaluated how ACDF influenced particular aspects of patients' quality of life in the context of radiological outcome. The study included 30 consecutive patients with single- or multi-level cervical disc herniation. Patients underwent clinical and radiological evaluation before and one year after the ACDF procedure. For each patient, we assessed the severity of cervical pain with a numerical rating scale (NRS) and filled the neck disability index questionnaire (NDI). The health-related quality of life was assessed with the Polish version of 36-Item Short Form Survey (SF-36). A significant decrease in all NDI aspects indicates a significant improvement after surgery. The quality of life in all aspects assessed with SF-36 scale was also improved. A moderate decrease in cervical spine mobility coexisted with a good outcome of the neurosurgical procedure. In the opinion of patients, the most important aspect after the cervical spine surgery is the reduction of pain severity. ACDF surgery is an effective method to reduce the severity of pain in patients with degenerative disc disease. ACDF improves the quality of patient's life. According to the study results the physical role improved most significantly; the least improvement was noted in role-emotional aspect. Up to 83% of patients achieved a reduction of the NDI index by 5 or more points after surgical treatment which proves the high effectiveness of the surgical treatment. No statistically significant difference was noted between patients with single and multi - level discopathy. Up to 97% of patients who underwent ACDF reported a significant decrease in pain severity measured with NRS.